Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Borana University - International Livestock Research Institute; Borana University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Borana University. On April 4, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Boku Tache, President of Borana University.